Analisis Kedisiplinan Belajar Siswa Kelas V SDN Suruhan Lor Kecamatan Bandung Kabupaten Tulungagung - Irpan Sodiq; Ria Fajrin Rizqy Ana (Jurnal Simki Postgraduate, 2023)
Discipline in learning is the goal of every educational institution so that a good education is formed, discipline in learning is a benchmark in the success of every educational institution. Students at SDN Suruhan Lor Bandung are in an environment where the majority of students fail in the educational process due to the large number of youth groups whose lack of knowledge is troubling the community, under these conditions a student study was conducted starting at the elementary education level. The purpose of this research is to describe the learning discipline of fifth grade students at SDN Suruhan Lor Bandung. The research method used is a qualitative method with the type of case study research. Data collection techniques through observation, interviews, and documentation. Data analysis used is data reduction, data presentation, and data verification. Discipline in student learning can be seen from the results of observations made by researchers on 15 fifth grade students at SDN Suruhan Lor, Bandung District, Tulungagung Regency, with the results of the ability to discipline student learning to obtain a good category with a percentage of 63.7%.